Endoscopic Aspiration and Marsupialization for Colloid CYST - Muhammad Adil Khatri, Farhad Ali, Irfan Ali Shah, Muhammad Asim Khan Rehmani, Shiraz Ahmed Ghori, Muhammad Faaiq Ali, Atiq Ahmed Khan, Muhammad Imran (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Colloid cyst is a benign intracranial tumor found in the anterior third ventricle. Due to location of this tumor, it has propensity to cause obstruction to CSF flow causing hydrocephalus. Treatment options include excision or aspiration of cyst through open or endoscopic procedures or CSF diversion procedures. Recent years have seen a shift towards endoscopic approach to treatment of colloid cyst due to its relative simplicity among endoscopic procedures and other favorable patient related factors. We share our experience with endoscopic aspiration and marsupialization of colloid cyst. Methods: This descriptive retrospective study was done at Neuro surgery department of Neurosurgery, SMBB Institute of Trauma, Dow University of Health Sciences, Dr. Ruth K. M. Pfau Civil Hospital Karachi, Pakistan. Data of patients who had endoscopic aspiration and marsupialization of colloid cyst between February 2017 and October 2020. Patient demographics, clinical presentation, radiological features, operative course and post-operative course was recorded. Clinical or radiologic recurrence was noted on follow-up. Results: Ten patients were operated during the study period. Headache was most common presenting symptom. Mean size of cyst was 21mm. There was incomplete aspiration in 3 patients as observed per-operatively and by residual cyst content on immediate post-operative CT scan which disappeared completely on subsequent scans. CSF leak was observed in 3 patients and 2 developed meningitis. No symptomatic recurrence occurred. Conclusion: Endoscopic aspiration with marsupialization of cyst wall is a safe and effective technique for treatment of colloid cyst. Incomplete aspiration of cyst contents may not require further intervention as the radiological resolution of cyst is observed over time. Further follow-up and larger sample size is needed to further establish the safety and efficacy of this procedure. Keywords: colloid cyst, endoscopic, follow-up studies